Preferences to Receive Information about Palliative Care for Adult Patients. Issue 2 (April 2020) - Pittroff, Gail; Hendricks-Ferguson, Verna
Abstract : ABSTRACT: This research study aimed to describe preferences about factors related to receiving information regarding medical treatments and palliative care (PC) options for adult patients with a poor prognosis and/or their primary decision maker. A single-group descriptive study design and content analysis were utilized. Seven trained registered nurse (RN) study team members conducted interviews to obtain narrative data. All study participants preferred to learn PC services earlier in the illness trajectory and desired to learn about this service from nurses. Most reported a desire to have spouses and family involved in decisions about PC. Nearly all wanted to understand PC options ahead of time should treatment not go as planned.